PHILOSOPHICAL DOUBTS ABOUT CONTROVERSY BETWEEN REASON AND EMOTION IN THE PROCESS OF MORAL UPBRINGING - Baranova, Jūratė (Acta Paedagogica Vilnensia, 2009)
This research is aiming to discover the arguments, formulated by two different, even opposite traditions, indicating the presuppositions for moral upbringing. The first one stressed the role of reason in moral upbringing (Socrates, Kant, Hare, Popper). On the other side, the other one (Hume, Scheler, Rorty, Williams), emphasized the role of emotions in the process of moral upbringing. The article analyses not only the differences between these two points of departure, but their incommensuarability as well. The author of the text comes to the conclusion, that this opposition, reaching contemporary philosophy of education as well is too exagerated and suggests to look for the harmony between these two personal powers – reason and emotion. According to her oppinion, the powers of imaginations unites the spheres of reason and emotion. Agreeing that the problem is not very simple and, as was shown by the analyzed authors, exegencies to one or the other side always are possible, nevertheles the purpose of moral upbringing could be based on the harmony between these two powers, using interdisciplinary aspects (philosophy, literature, visual arts) preparing programs for moral upbringing.
Keywords: reason; feeling; imagination; moral upbringing